Hypertension and Diabetes Mellitus Increase the Risk of Stroke - Sofiana, Liena; Rahmawati, Dwy Desy (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Stroke is one of the cause of death and major neurological disability in Indonesia. The risk of stroke increases with the number of risk factors. Stroke is the main cause of inpatient death at Panembahan Senopati General Hospital in Bantul. The independent variables in this study were hypertension and diabetes mellitus. This study aim to determine the relationship of hypertension and diabetes mellitus to the incidence of stroke. The study was conducted in 2016 and was an observational analytic study with cross sectional design. The number of respondents were 256 samples, where samples were taken by simple random sampling. The research instrument is observation sheet of medical records. Analysis of data was conducted using univariate and bivariate analysis using chi-square test. Bivariate analysis showed significant correlation statistically and biologically between hypertension (RP = 9.000 ; CI = 4.866-16.645 ; p value = 0.000) and diabetes mellitus (RP = 4.226 ; CI = 3.089-5.780 ; p value = 0.000) with the incidence of stroke. Efforts to increase health promotion program to improve community awareness regarding the incidence of stroke are suggested to improve the quality of life of stroke patients.